The Influence of SDG Disclosure and Islamic Social Reporting on Islamic Ethical Responsibility and Maqasid Sharia Performance in Sharia Banks in Indonesia for the 2020–2025 Period. - Sri Depi; Amiruddin; Asri Usman (GoodWill, 2026)
This study examines the effect of SDGs Disclosure and Islamic Social Reporting (ISR) on Maqasid Sharia Performance with Islamic Ethical Responsibility as a mediating variable in Islamic banks in Indonesia during the 2020–2025 period. The research addresses the gap in integrating global sustainability frameworks with Islamic ethical principles in measuring sharia-based performance. The main objective of this study is to analyze the direct and indirect relationships between SDGs Disclosure, ISR, Islamic Ethical Responsibility, and Maqasid Sharia Performance. This research employed a quantitative explanatory approach using secondary data derived from annual reports of Islamic commercial banks, selected through purposive sampling. Data were analyzed using multiple linear regression and mediation testing with SPSS. The results show that SDGs Disclosure has a positive and significant effect on Islamic Ethical Responsibility, although with a relatively small contribution, and does not significantly affect Maqasid Sharia Performance. In contrast, Islamic Social Reporting has a strong positive and significant effect on both Islamic Ethical Responsibility and Maqasid Sharia Performance. Furthermore, Islamic Ethical Responsibility partially mediates the relationship between ISR and Maqasid Sharia Performance but does not effectively mediate the influence of SDGs Disclosure. These findings highlight that ISR plays a more substantial role than SDGs Disclosure in enhancing ethical responsibility and achieving maqasid-based performance. This study contributes to the development of Islamic accounting literature by integrating sustainability and sharia performance concepts, and provides practical implications for improving social reporting quality in Islamic banking.